2019
DOI: 10.2134/agronj2018.08.0534
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Traits in Durum Wheat Germplasm Possessing Puroindoline Genes

Abstract: Durum wheat (Triticum turgidum subsp. durum) represents only 5% of global wheat production. Durum production is limited by its very hard kernel texture, which requires specialized milling and limits end-product utilization. However, soft kernel durum wheat was recently developed to remove these constraints, but it has not until now been examined for its agronomic potential and pest resistance, which were the focus of this study. The soft durum lines were compared with two commercial hard red spring wheat varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…More detailed agronomic performance of Soft Svevo and Salzburg are described in Kiszonas et al. (2019) wherein ‘Salzburg’ = ‘SALZ‐1’.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed agronomic performance of Soft Svevo and Salzburg are described in Kiszonas et al. (2019) wherein ‘Salzburg’ = ‘SALZ‐1’.…”
Section: Characteristicsmentioning
confidence: 99%
“…Results of the 2020 trial indicated that USDA Lori had grain yield similar to that of Soft Svevo and Salzburg (Table 2). More detailed agronomic performance of Soft Svevo and Salzburg are described in Kiszonas et al (2019) wherein 'Salzburg' = 'SALZ-1'. Grain volume weight ("test weight") of USDA Lori was similar to somewhat less than Louise (Table 1).…”
Section: Agronomic Performancementioning
confidence: 99%
“…With the caveat of dough water absorption, soft kernel texture and bread quality are not in opposition to one another. The soft kernel trait itself appears to exert no negative affect on yield, agronomic performance or pest resistance (Kiszonas et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Durum wheat can be considered a major but underutilized crop globally. Although durum possesses some advantages over bread wheat in terms of pest resistance, abiotic stress resistance, and agronomic performance (Kiszonas et al., 2019, and references therein), the widely held view is that it is inferior for bread baking. The reason for this inferiority is described in terms of either weak and/or inextensible gluten.…”
Section: Discussionmentioning
confidence: 99%